KAJIAN PERBEDAAN TEKANAN DARAH SISTOLE DAN DIASTOLE PADA PASIEN STROKE - Awan, Awan Hariyanto (STIKES dan AKZI Karya Husada Kediri, 2024)
Stroke is a disease that requires special attention because a stroke can have fatal consequences due to functional brain disorders which can occur suddenly. One of the nursing actions for stroke patients is monitoring blood pressure with the aim of early detection to prevent the risk of recurrent stroke. Blood pressure measurements can be carried out on extremities that experience weakness and those that do not experience weakness. The research aims to determine the difference in systolic and diastolic blood pressure measurements in stroke patients between extremities that experience weakness and those that do not experience weakness. The research design used was quantitative descriptive. The population used was 86 stroke patients in the Stroke Unit of RSUD dr. Soedomo Trenggalek with a total sample of 46 stroke patients using a purposive sampling method. The analysis used is descriptive frequency distribution. The results of the study showed that from 46 respondents who were measured based on the difference in systolic and diastolic blood pressure between the extremities that experienced weakness and the extremities that did not experience weakness, it showed that the majority of 28 stroke patients (61%) had no difference in systolic blood pressure, while the majority for diastolic blood pressure was 35 ( 76.1%) There is also no difference between the extremities that experience weakness and those that do not experience weakness. The conclusion of the results of this study is that there is no difference in systolic and diastolic blood pressure values ​​in stroke patients between the extremities that experience weakness and those that do not experience weakness.